Prostate Cancer Vaccines: Progress, Challenges, and Future Directions - Runtunuwu, Stefanus Vicky Bernhard Elisa; Tallei, Trina Ekawati; Turalaki, Grace Lendawati Amelia (Heca Sentra Analitika, 2025)
Prostate cancer remains a major contributor to cancer-related deaths in men, with its incidence rising significantly with age. Conventional treatment modalities, including surgery, radiation therapy, hormonal therapy, and chemotherapy, often face limitations such as treatment resistance, disease recurrence, and considerable side effects. These challenges have sparked growing interest in novel approaches like immunotherapy, which leverages the immune system to combat cancer. Among these, vaccine-based immunotherapy has emerged as a promising strategy, aiming to generate precise immune responses against tumor-specific antigens. Advances in immunology, molecular targeting, and vaccine development have demonstrated encouraging results in terms of safety and immunogenicity. Nevertheless, obstacles such as tumor heterogeneity, immune escape mechanisms, and limited efficacy in advanced stages of the disease continue to hinder progress. The aim of this review is to examine the current landscape of prostate cancer vaccine development, with a focus on advancements in molecular target identification, optimization of vaccine technologies, and the evaluation of combination therapy strategies. Findings from clinical trials have shed light on both the opportunities and challenges of vaccine-based therapies. Synergistic approaches involving immune checkpoint inhibitors, radiotherapy, and androgen deprivation therapy have shown potential to amplify immune responses and mitigate resistance mechanisms. Additionally, emerging technologies such as bioinformatics and artificial intelligence are revolutionizing vaccine development by enabling the discovery of patient-specific neoantigens and the creation of tailored vaccine formulations. Despite these breakthroughs, achieving consistent therapeutic outcomes remains challenging, particularly in metastatic and castration-resistant cases. Future directions in the field include developing personalized cancer vaccines, adopting adaptive clinical trial designs, and employing innovative endpoints to streamline translation into clinical practice. In summary, while prostate cancer vaccine development has advanced significantly, addressing critical barriers like tumor heterogeneity and immune evasion and embracing emerging technologies are essential for optimizing personalized vaccines and improving treatment outcomes.